The Light Design in Exhibition Spaces - Song, Bin; Puntien, Pisit; Inkuer , Akapong; Mayusoh, Chanoknart (Journal of Roi Kaensarn Academi, 2024)
The light design in the exhibition space plays a vital role in the exhibition space and has irreplaceable value. At the same time, excellent light design also plays a positive role and influence in the communication of excellent exhibition space design. This article mainly uses qualitative research methods combined with appropriate quantitative analysis and comprehensive analysis. After studying a large number of relevant literature and cases, it is concluded that the light design in the exhibition space is thematic, dramatic, diverse and integrated. These characteristics improve the design effect of the display space, help achieve the design goals of the display space, promote the communication and development of the display space, and fully reflect the importance, role, value and influence of light design on the display space and the communication of the display space.